DigestiFlow: from BCL to FASTQ with ease - Holtgrewe, Manuel (Bioinformatics, 2020)
SUMMARY: Management of raw-sequencing data and its pre-processing (conversion into sequences and demultiplexing) remains a challenging topic for groups running sequencing devices. They face many challenges in such efforts and solutions ranging from manual management of spreadsheets to very complex and customized laboratory information management systems handling much more than just sequencing raw data. In this article, we describe the software package DigestiFlow that focuses on the management of Illumina flow cell sample sheets and raw data. It allows for automated extraction of information from flow cell data and management of sample sheets. Furthermore, it allows for the automated and reproducible conversion of Illumina base calls to sequences and the demultiplexing thereof using bcl2fastq and Picard Tools, followed by quality control report generation. AVAILABILITY AND IMPLEMENTATION: The software is available under the MIT license at https://github.com/bihealth/digestiflow-server. The client software components are available via Bioconda. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.